Asymmetric remote C-H functionalization: use of internal olefins in tandem hydrometallation-isomerization-asymmetric conjugate addition sequences - Mola, L; Sidera, M; Fletcher, S (CSIRO Publishing, 2015)
We describe catalytic asymmetric C-C formation using terminal alkyl-metal nucleophiles generated from internal olefins through a 'chain-walking' isomerization mechanism. Hydrometallation of internal olefins with the Schwartz reagent gives the least hindered alkyl-zirconocene after thermal (60°C in THF) isomerization. After switching the solvent from THF to dichloromethane, the alkyl-zirconocenes can be used in copper-catalyzed asymmetric conjugate additions. Addition to a variety of cyclic α,β-unsaturated species were achieved in modest (22-50%) yield with high (84-92% ee) enantioselectivity. This work demonstrates that remote C-H functionalization coupled with asymmetric C-C bond formation is possible, but the present procedures are limited in terms of yield and olefin scope.